Efektivitas Layanan Perpustakaan di Kantor Arsip Perpustakaan Kota Payakumbuh - Izzaty, Mawaddathul; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
The purpose of writing this article, namely: (1) describe the effectiveness of library services in the Office of Archives and Library Payakumbuh; (2) describe the obstacles encountered in providing the services and efforts will be made so that the implementation of optimal and effective service. Data were collected by means of observation, interviews with librarians and questionnaire (questionnaire) with user library at the Office of Archives and Library Payakumbuh. The method used is descriptive and quantitative methods. Based on the results of the research, concluded as follows: (1) the effectiveness of library services in the Office of Archives and Library Payakumbuh not gone well, especially in the service retrieval, circulation services, reference services, services periodicals; (2) obstacles encountered in providing services is the lack of infrastructure, policies librarians in providing services to users is not optimal, the collection has not been prepared based classification, borrowing and repayment collections too long; and efforts is to add infrastructure and librarians noticed policies to be taken, the collection should have been prepared based on the classification, borrowing and repayment need not be too long.Â Keywords: Effectiveness, services, library